Dinamika Sosial Sebagai Landasan Perubahan Qaul Qadim dan Qaul Jadid dalam Pemikiran Al-Syafi’i - Munir, Misbahul; Misbahuddin, Misbahuddin; Kurniati, Kurniati (Journal of Comprehensive Science, 2025)
The results of a Mujtahid's Ijtihad can change. Therefore, differences in the results of Ijtihad are often found between one Mujtahid and another scholar. Even one scholar or Mujtahid can have different new ijtihad results with the old ijtihad results on the same issue. This research analyses the role of social factors in changes in Imam al-Syafi'i's legal thinking, which is focused on the validity and how likely social factors affect changes in al-Syafi'i's ijtihad in Qaul Qadim and Qaul Jadid. This type of research is library research that focuses on library sources in the form of books and journals that are relevant to understanding the validity or how much the role of social context in changing al-Syafi'i's thinking. The results showed that social conditions can only be one of the considerations for the change in al-Syafi'i's ijtihad in Qaul Qadim and Qaul Jadid, because a Mujtahid must understand fiqh al-waqi' (fiqh of reality). However, the main factor in the change of opinion on Qaul Qadim and Qaul Jadid is the change in tarjih al-adillah (superiority of arguments) both Naqli arguments (al-Qur'an, Hadith, Atsar) and Aqli arguments (Ijma', Qiyas).